Country Partnership Framework for the Republic of Costa Rica for the Period FY16-FY20 - World Bank Group (World Bank, Washington, DC, 2015)
Costa Rica stands out for being one of the most politically stable, progressive, and prosperous nations in Latin America and the Caribbean (LAC). Political stability and inclusive social policies have contributed to solid growth rates and the modernization of the country. The combination of political stability, the social compact and steady growth, has resulted in one of the lowest poverty rates in LAC. Costa Rica is also a global leader for its environmental policies and accomplishments, which have helped the country to build its Green Trademark. The pioneering payments for environmental services program has been successful in promoting forest and biodiversity conservation and Costa Rica is the only tropical country in the world that has reversed deforestation. Two pressing development challenges stand out: the deteriorating fiscal situation and stubborn inequality. These challenges cut across the fabric of Costa Rica’s development model and affect the basic pillars of development: inclusion, growth, and sustainability. The new government seeks to address these problems and is committed to an inclusive society that guarantees the welfare of its people, supported by transparent and accountable public institutions. The World Bank Group’s (WBG’s) new country partnership framework (CPF) seeks to support Costa Rica’s objectives of reducing constraints to productive inclusion and bolstering fiscal, social, and environmental sustainability.